Further delineation of putative ACTB loss‐of‐function variants: A 4‐patient series. Issue 4 (16th January 2020) - Baumann, Matthias; Beaver, Erin M.; Palomares‐Bralo, María; Santos‐Simarro, Fernando; Holzer, Peter; Povysil, Gundula; Müller, Thomas; Valovka, Taras; Janecke, Andreas R.
Abstract: ACTB encodes β‐cytoplasmic actin, an essential component of the cytoskeleton. Based on chromosome 7p22.1 deletions that include the ACTB locus and on rare truncating ACTB variants, a phenotype resulting from ACTB haploinsufficiency was recently proposed. We report putative ACTB loss‐of‐function variants in four patients. To the best of our knowledge, we report the first 7p22.1 microdeletion confined to ACTB  and the second ACTB frameshifting mutation that predicts mRNA decay. A de‐novo ACTB p.(Gly302Ala) mutation affects β‐cytoplasmic actin distribution. All four patients share a facial gestalt that is distinct from that of individuals with dominant‐negative ACTB variants in Baraitser‐Winter cerebrofrontofacial syndrome. Two of our patients had strikingly thin and sparse scalp hair. One patient had sagittal craniosynostosis and hypospadias. All three affected male children have attention deficits and mild global developmental delay. Mild intellectual disability was present in only one patient. Heterozygous ACTB deletion can allow for normal psychomotor function. Abstract : ACTB encodes β‐cytoplasmic actin, an essential component of the cytoskeleton. Based on rare chromosome 7p22.1 deletions that include the ACTB locus and on rare truncating ACTB variants, a phenotype resulting from ACTB haploinsufficiency was recently proposed. We report the first 7p22.1 microdeletion confined to ACTB, and the second ACTB frameshifting mutation that predicts mRNA decay. Mild intellectual disability was present in one patient. Attention deficits and mild global developmental delay were present in three patients. Normal psychomotor function was seen in one patient with a heterozygous ACTB deletion. Heterozygous ACTB deletion can allow for normal psychomotor function.